Perencanaan Strategis Sistem Informasi Menggunakan Enterprise Architecture Planning dan Pendekatan SDLC - Nabila Sasgita; Widia Putri Febriani; Wilda Putri Sabila; Tikooo Nurhalizaaaaaaa (Algoritma: Jurnal Ilmu Komputer dan Informatika, 2025)
Strategic Information Systems (IS) planning is an essential aspect in supporting organizational objectives through the effective and integrated use of information technology. However, the implementation of IS at the Muaro Jambi Education Office still encounters challenges, including fragmented data management across various work units and the use of non-integrated applications, resulting in suboptimal support for strategic decision-making. This study aims to develop strategic IS planning using the Enterprise Architecture Planning (EAP) method with the System Development Life Cycle (SDLC) approach to align business requirements with data, application, and information technology architectures. The research employed a case study method through interviews, business process observation, and literature review. The EAP stages were applied to design business, data, application, and technology architectures, while the SDLC approach was applied in a limited manner at the analysis and system design stages as a systematic framework supporting the formulation of information system architecture. Supporting analyses included Value Chain modeling, SWOT analysis, and application portfolio mapping using the McFarlan Strategic Grid. The results indicate that information system integration has not been optimally achieved despite the availability of technological infrastructure. This study produces an architectural blueprint and an implementation roadmap as a foundation for integrated and sustainable IS planning. Keywords: Enterprise Architecture, Education Office, Enterprise Architecture Planning, Strategic Planning, Information Systems